L (R) Cyclic Semigroups Satisfying the Identity: abc = ca - D.D. , Padma Priya; G. , Srinivasa; G. , Shobhalatha; R. , Bhuvana Vijaya (International Journal of Psychosocial Rehabilitation, 2020)
Semigroups, being one of the algebraic structures, are sets with an associative binary operation defined on them. The theory of semigroups satisfies additional properties like commutativity, left (right) cyclic i.e., L(R) cyclic, left (right) identity, left (right) cancellative, and many others. In this paper we determine different structures of semigroups like normal, seminormal, quasinormal, semiregular, and others by using the identity abc = c with the concept of L(R) cyclic properties of semigroups.